Plant communities on ironstone outcrops: a diverse and endangered Brazilian ecosystem - Jacobi, Claudia M; do Carmo, Flávio F; Vincent, Regina C; Stehmann, João R (Biodiversity and conservation, 2007)
Mountain areas are recognized centres of endemism and diversity on account of their isolation and altitudinal diversity. In tropical regions, mountain tops usually stand as islands of xeric vegetation among mesophytic assemblages. Unlike the vegetation growing on other rock outcrops lithologies, such as inselbergs (granite/gneiss) or campos rupestres (quartz/arenite), ironstone outcrop plant communities still lack systematic studies in Brazil. These outcrops (locally known as canga) share most of the characteristics of other rock outcrops, such as isolation and edapho-climatic harshness, but differ in that they are the object of opencast mining, and thus subjected to irrecoverable degradation. In addition, they are expected to harbour metal-tolerant and hyperaccumulator plant species. A botanical survey of two ironstone outcrop locations in the most important mining region of southeastern Brazil, the Iron Quadrangle, revealed a high within-site (138 and 160 species per site), and between-site diversity (only 27% of common species), totaling 64 families and 234 species among basal families and eudicots (154 species), monocots (68 species), and ferns (12 species). Canga crusts are rich in dicots, several of which play an important role in community structuring, together with the more usual monocot aggregations. Distinct plant communities are found associated to different microhabitats within the iron crust, depending primarily on the amount of soil and moisture retention in the different microtopographies. The environmental uniqueness, high diversity, lack of studies and rapid destruction of these ecosystems pose an immediate challenge for their conservation.